2015
DOI: 10.1007/s10722-015-0272-0
|View full text |Cite
|
Sign up to set email alerts
|

Salt tolerance in wild relatives of adzuki bean, Vigna angularis (Willd.) Ohwi et Ohashi

Abstract: Salt stress is becoming a serious problem in food production field. To find sources of salt tolerance, we screened 74 accessions of adzuki bean (Vigna angularis) and 145 accessions of cross-compatible wild relatives (seven species). We performed the primary screening in soil culture and the secondary screening in hydroponic culture, and identified JP205833 of V. riukiuensis (strain 'Tojinbaka') and JP107879 of V. nakashimae (strain 'Ukushima') as the valuable source of salt tolerance. We found these two strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 14 publications
2
56
0
Order By: Relevance
“…The bottom half of each pot was then immersed in the pool. We set the moderate salt stress at 50 mM NaCl for two weeks according to our previous study in which sensitive accessions severely wilted within two weeks even at 50 mM NaCl concentration [ 12 ]. We also set the severe stress condition of 200 mM NaCl for two weeks so that we could evaluate the differences in more tolerant accessions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bottom half of each pot was then immersed in the pool. We set the moderate salt stress at 50 mM NaCl for two weeks according to our previous study in which sensitive accessions severely wilted within two weeks even at 50 mM NaCl concentration [ 12 ]. We also set the severe stress condition of 200 mM NaCl for two weeks so that we could evaluate the differences in more tolerant accessions.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, we identified two salt tolerant accessions (ID 17 and 18 in this study) from wild germplasm, which are cross compatible with azuki bean ( V . angularis ), an important Vigna crop in East Asia [ 12 ]. In another study, genetic analysis on a beach species V .…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that sodium movement might be restricted by the membranes of certain extrastelar tissue, excluding it from the vascular system. According to Yoshida et al (2016), the autoradiographs of bean stomatal density (Reyes-López et al, 2015), which provides a greater distance between the stomata, leading to a reduced transpiration. There is a hypothesis that, despite morphological and physiological differences, a species may have stress tolerance mechanisms and remediation expressed by metabolic changes induced by salinity and drought.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, 100 μL of 1 N HNO 3 was added for cation extraction. The leaf Na + and K + concentrations were determined using an ion chromatograph with a conductivity detector (Shimadzu, Japan) and in accordance with our previous study (Yoshida et al, 2016). Oxalic acid (3.3 mM) was used as the mobile phase.…”
Section: Ion Chromatographmentioning
confidence: 99%
“…The quantification of Na + and K + concentrations in plant tissues is widely performed using flame photometer, atomic absorption spectrophotometry, or ion chromatography (Vera-Estrella et al, 2005;Wang et al, 2012;Yoshida et al, 2016). These methods are accurate and reliable, even for samples with low ion concentrations.…”
Section: Introductionmentioning
confidence: 99%